2020
DOI: 10.29102/clinhp.20003
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Well-Reported Implementation: Fast-IM and RE-AIM

Abstract: Background Implementation in healthcare is often slow and poorly reported. Results include suboptimal outcomes and adverse consequences for patients. However, promising tools to remedy implementation speed and reporting already exist – such as the evidence-based, fast-track implementation model (Fast-IM) and the comprehensive RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) reporting format. Metods In combination, Fast-IM and RE-AIM may constitute a new best practice for fast and well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the survey of the implemented course (spring 2019) (Table 4), the median participant satisfaction was 6 [5,7] on a Likert scale from 1-7. All the students found that the course provided them with knowledge that would be concretely useful in the future.…”
Section: Implemented Course: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…In the survey of the implemented course (spring 2019) (Table 4), the median participant satisfaction was 6 [5,7] on a Likert scale from 1-7. All the students found that the course provided them with knowledge that would be concretely useful in the future.…”
Section: Implemented Course: Surveymentioning
confidence: 99%
“…However, the development of proper curricula often skips the needs assessment and definition of goals and objectives and goes straight to defining educational strategies. Once the training curricula have been developed, another often-seen problem is that they are poorly implemented [4], although examples exist of implementation models tested in real life with promising results [5]. Thus, a plan for curriculum implementation should be an essential component when developing course curricula in medical education.…”
Section: Introductionmentioning
confidence: 99%